Legality and venture governance around the world - Douglas Cumming; Daniel Schmidt; Uwe Walz (Goethe University Frankfurt, Center for Financial Studies (CFS), 2004)
We analyze governance with a dataset on investments of venture capitalists in 3848 portfolio firms in 39 countries from North and South America, Europe and Asia spanning 1971-2003. We find that cross-country differences in Legality have a significant impact on the governance structure of investments in the VC industry: better laws facilitate faster deal screening and deal origination, a higher probability of syndication and a lower probability of potentially harmful co-investment, and facilitate board representation of the investor. We also show better laws reduce the probability that the investor requires periodic cash flows prior to exit, which is in conjunction with an increased probability of investment in high-tech companies.
urn:nbn:de:hebis:30-10681
Keywords: G24; G31; G32; 330; Venture Capital; Corporate Governance; Syndication; Entrepreneurial Finance; Risikokapital; Aktienfonds; Portfolio-Management; Aktienrecht; Corporate Governance; Welt